Species Delimitation and Interspecific Relationships of the Genus Orychophragmus (Brassicaceae) Inferred from Whole Chloroplast Genomes - Hu, Huan; Hu, Quanjun; Al-Shehbaz, Ihsan A.; Luo, Xin; Zeng, Tingting; Guo, Xinyi; Liu, Jianquan (Frontiers in Plant Science, 2016)
Introduction It is rather difficult to delimit recently diverged species and construct their interspecific relationships because of insufficient informative variations of sampled DNA fragments (Schluter, 2000; Arnold, 2006). The genome-scale sequence variations were found to increase the phylogenetic resolutions of both high- and low-taxonomic groups (e.g., Yoder et al., 2013; Lamichhaney et al., 2015). It is still expensive to collect nuclear genome variations between species for most none-model genera without the reference genome. However, chloroplast genomes (plastome) are relatively easy to be assembled to examine interspecific relationships for phylogenetic analyses, especially in addressing unresolved relationship at low taxonomic levels (Wu et al., 2010; Nock et al., 2011; Yang et al., 2013; Huang et al., 2014; Carbonell-Caballero et al., 2015). Plastomes are haploid with maternal inheritance in most angiosperms (Corriveau and Coleman, 1988; Zhang and Liu, 2003; Hagemann, 2004) and are highly conservative in gene order and genome structure with rare recombinations (Jansen et al., 2007; Moore et al., 2010). In this study, we aimed to examine species delimitation and interspecific relationships in Orychophragmus through assembling chloroplast genomes of multiple individuals of tentatively delimited species (Hu et al., 2015a). Orychophragmus is a small genus in the mustard family (Brassicaceae, Cruciferae) distributed in northern, central, and southeastern China (Zhou et al., 2001). Its plants have been widely cultivated as ornamentals, vegetables, or source of seed oil (Sun et al., 2011). Despite controversial species delimitations in the genus (Zhou et al., 1987; Tan et al., 1998; Wu and Zhao, 2003; Al-Shehbaz and Yang, 2000; Zhou et al., 2001; Sun et al., 2012), our recent study based on nuclear (nr) ITS sequence variations suggested the recognition of seven species (Hu et al., 2015a). Orychophragmus is sister to Sinalliaria, which is a genus endemic to China with one (Zhou et al. 2014) or two independent species (Hu et al. 2015a). Nuclear ITS sequence variations support the recognition of seven species and strongly resolve their interspecific relationships, but four DNA fragments (matK, rbcL, trnH-psbA, and trnL-F) of the chloroplast genome failed to do so (Hu et al., 2015a). It was hypothesized that this was caused by